2011
DOI: 10.1007/s00595-011-0100-x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic comparison of cervical and extra-cervical surgical approaches for endoscopic thyroidectomy

Abstract: Evaluation of the different surgical approaches for endoscopic thyroidectomy shows that the incidence of hemorrhage and seroma are higher in the extra-cervical group, but the rate of conversion to conventional open surgery is significantly higher in the cervical group. Furthermore, patients who undergo extra-cervical endoscopic thyroidectomy are associated with longer operating time and hospital stays; however, these studies suggest that the extra-cervical surgical approach for endoscopic thyroidectomy is pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 33 publications
1
20
1
Order By: Relevance
“…Arterial bleeding and large tumor size are both difficult to deal with under endoscopic procedures in comparison to open surgery. And Geng-Zhen et al [11] reported that the conversion rate was 2.21% in the cervical group, higher than that in extracervical group (0.42%). On the other hand, there is still limited evidence provided by multicentral, big sample, prospective studies that SET can provide a satisfied recurrence rate.…”
Section: Advantages and Disadvantagesmentioning
confidence: 99%
“…Arterial bleeding and large tumor size are both difficult to deal with under endoscopic procedures in comparison to open surgery. And Geng-Zhen et al [11] reported that the conversion rate was 2.21% in the cervical group, higher than that in extracervical group (0.42%). On the other hand, there is still limited evidence provided by multicentral, big sample, prospective studies that SET can provide a satisfied recurrence rate.…”
Section: Advantages and Disadvantagesmentioning
confidence: 99%
“…Another potential disadvantage is the longer operative time and considerable learning curve associated with extracervical approaches. All techniques require a larger dissection area and resultant longer surgical approach leading to increased operative time [98]. With all reported techniques included in this review, increased experience and improved surgical techniques will reduce operative time closer and closer to that of conventional techniques.…”
Section: Discussion Of Endoscopic Approachesmentioning
confidence: 99%
“…Operative complications in extracervical approaches are similar to those found in conventional thyroidectomy with added unique complications of subcutaneous emphysema, chest wall paraesthesia, and seroma (14,17 from Johri 2018). Initial studies reported higher rates of complications [17, 3943] which have reduced to rates comparable to conventional techniques with improvement of surgical skills and instruments [98]. Perhaps the most important complications of thyroid surgery are parathyroid gland and RLN injury.…”
Section: Discussion Of Endoscopic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] On the other hand, although some authors have reported similar radical removal in malignant cases, 7 tumor colonization of the subcutaneous tract has already been described. 8 In my opinion, all these techniques can be used in selected patients, especially if they have a history of keloid formation, but I do not think these will replace the classical incision, at least in the Western world.…”
mentioning
confidence: 92%